Pendampingan Pembuatan Desain Dan Rab Untuk Pembangunan Masjid Baiturrahim Serampon, Licin - Banyuwangi - Purnomo, Dimas Aji; Prisilia, Harliwanti; Nugroho, Heru Prasetyo (Abdi Panca Marga, 2022)
The difficulties experienced by the people of Serampon village in planning the mosque are how to design a mosque that is both architecturally and functionally, how to plan and calculate the strength of its structure and how to calculate the cost for its construction. So that the existence of a community service team from the Faculty of Engineering, University of 17 August 1945, Banyuwangi, is expected to be able to plan the design of the Baiturrahim Mosque. The implementation stages for this activity are field surveys, compiling measurement data, site analysis and circulation space, making planning drawings. The design concept uses architectural aspects by considering lighting, air circulation and environmental conditions. Based on the results of structural calculations for concrete portals, the main reinforcement is 16 mm in diameter and 10 mm in stirrups. Based on the results of the calculation of the budget plan (RAB) for the Baiturrahim Mosque, Serampon Village, a total cost of Rp.895.478.000,00 Keywords: Mosque, Serampon village, Calculation of the budget plan